Experimental Observation of Strong Exciton Effects in Graphene Nanoribbons - Tries, Alexander; Osella, Silvio; Zhang, Pengfei; Xu, Fugui; Ramanan, Charusheela; Klaeui, Mathias; Mai, Yiyong; Beljonne, David; Wang, Hai (Nano Letters, 2020)
Graphene nanoribbons (GNRs) with atomically precise width and edge structures are a promising class of nanomaterials for optoelectronics, thanks to their semiconducting nature and high mobility of charge carriers. Understanding the fundamental static optical properties and ultrafast dynamics of charge carrier generation in GNRs is essential for optoelectronic applications. Combining THz spectroscopy and theoretical calculations, we report a strong exciton effect with binding energy up to ∼700 meV in liquid-phase-dispersed GNRs with a width of 1.7 nm and an optical band gap of ∼1.6 eV, illustrating the intrinsically strong Coulomb interactions between photogenerated electrons and holes. By tracking the exciton dynamics, we reveal an ultrafast formation of excitons in GNRs with a long lifetime over 100 ps. Our results not only reveal fundamental aspects of excitons in GNRs (strong binding energy and ultrafast exciton formation etc.) but also highlight promising properties of GNRs for optoelectronic devices.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Exciton binding energy; Exciton formation; Excitons; Graphene nanoribbons; THz spectroscopy